Predictors of missed hospital appointments in patients with posterior compartment pelvic floor disorders in a tertiary referral centre - Tanzeela Gala; Mehak Saini; Abigail Fernandes; Carlotta Sarzo; Noman Shahzad; Carlene Igbedioh; Alexis Schizas; Linda Ferrari; Alison Hainsworth (Continence)
Aim:: Missed hospital appointments pose a major challenge to the healthcare system leading to worse patient outcomes. We ascertained the incidence of missed hospital appointments in patients with Posterior Compartment Pelvic Floor Disorders (PC-PFD) and associated socio-demographic and clinical predictors. Methods:: This is a cross-sectional single-institution study from a tertiary pelvic floor unit (PFU) with data collected from a prospectively maintained database.A missed appointment was marked if patients did not​ attend two consecutive appointments without informing or asking to re-schedule and were recorded for Telephone Triage Assessment Clinic (TTAC), Specialist-nurse, face-to-face bowel function clinic (BFC), Investigations including endoanal (EAUS) and pelvic floor ultrasound (PFUS) and defaecating proctogram (DP). All results yielding p<0.05 were considered significant. Results:: PFU received 2001 referrals between 2013 and 2019 with a mean age of 52 years. Missed appointments recorded were: TTAC — 45 (2.2%), BFC — 309 (15.8%), EAUS — 476(24%), PFUS — 484(37.2%) and DP — 432(26.2%).Predictors determined were: Male gender, age <50 years, complaints of rectal pain and bleeding for missing telephone and face-to-face appointments, low socioeconomic status for missing face-to-face appointments, and mixed and other ethnic groups with missing telephone appointments. Conclusion:: This is the first study to report the incidence and socio-demographic and clinical predictors for missed appointments in patients with PC-PFD. Future prospective research, including qualitative studies interviewing patients, is needed to identify and address potential barriers patients face when accessing care for PC-PFD. This will help improve patient care and allow better utilisation of already constrained healthcare resources.